Tim Burton's The nightmare before Christmas [videorecording (DVD)] - Burton, Tim, 1958-; Selick, Henry; Elfman, Danny; Sarandon, Chris; O'Hara, Catherine; Hickey, William, 1928-1997; Shadix, Glenn; Reubens, Paul, 1952-; Page, Ken; Ivory, Ed; Lee, Christopher, 1922-2015 (Walt Disney Studios Home Entertainment : Distributed by Buena Vista Home Entertainment, 2008)
Jack Skellington is the King of Halloween. He becomes bored with the same routine every year. He decides to take a walk in the woods. There, he discovered a door leading to Christmastown and decides to spread Christmas joy to the world. When he is back in Halloweentown he shows his friends what Christmas is like, and he suggests doing Christmas this year instead. But things do not go as planned when Oogie Boogie, an evil gambling boogey man, plots to play a game with Santa Claus' life and creates a nightmare for all the good little boys and girls everywhere. Although Sally attempts to stop him, Jack embarks into the sky on a coffin-like sled pulled by skeletal reindeer.